Growth and yield response of 457 purple sweet potato (Ipomoea batatas) to different rates of potassium fertilizer - Wan Abd Aziz, Wan Nur Diyana (2015)
A study was conducted to determine the growth and yield response of 457 purple sweet potato (Ipomoea batatas) to different rates of potassium fertilizer. The objectives of the study were (i) to identify the optimum rate of potassium fertilizer for maximum growth of 457 purple sweet potato and (ii) to evaluate the yield performance of 457 purple sweet potato grown with different rates of potassium. The experiment was carried out at Field 2, Universiti Putra Malaysia Serdang, Selangor. The vines used as planting materials of 457 purple sweet potato were collected from Felda Raja Alias, Jempol, Negeri Sembilan and there were propogated at Field 2 for two months before been planted in the experimental plot. Stem cuttings of 25 cm in length were used. In total there were 460 stem cuttings grown in 20 experimental plots. The application of potassium fertilizer was divided into 3 stages: at the 3rd, 5th and 8th week after sowing. Muriate of Potash (MOP) was the source of potassium and was applied with five different rates: 0 (control), 80, 120, 160 and 200 kg ha-1. Each treatment had four replications. Data on maximum leaf number, maximum total dry weight, total fresh weight of tubers, leaves and vines, total dry weight of tubers, leaves and vines, maximum leaf area index (LAI) were measured in this study. The design of the experiment was a Randomized Complete Block Design (RCBD) and data obtained were analyzed using Analysis of Variance (ANOVA) with the Statistical Analysis System (SAS) software. The application of different rates of potassium fertilizer did not show any significant effect on the growth and yield of 457 purple sweet potato. Since there was no significant difference found, the application of the optimum rate of potassium fertilizer for growth and yield of 457 purple sweet potato cannot be recommended.